The Proliferation of a New Market Disruptive Innovation: Personal 3D Printers (International Journal of Current Engineering and Technology, 2015)
The new technology uses various materials and innovations where some of the relevant employ plastic filament extruded through a nozzle. In other words, 3D printing technology is linked to the third industrial revolution plus a technology that have the potential and ability of changing the world in a better angle. Disruption is an ideal example that continues to be a tremendous source of various growth concepts in the economic setting. The theory of disruptive innovations is with no doubt the most and used innovation theory that is influential.
Keywords: Disruptive; Technology; Innovation; 3D Printers; New Market; Proliferation